IDENTITY AS A SOCIOCULTURAL FACTOR AND A SOURCE OF MODERN ETHNIC CONFLICTS - Yuryevich Zelenkov, Mikhail; Veretennikova, Irina; Erzyileva, Irina; Zubov, Vadim; Mamaeva, Yuliya (Gênero & Direito, 2020)
Ethnic conflict as a destructive phenomenon of modern human civilization is the object of the study. The specific subject under examination is identity that presents one of the characteristic foundations of an ethnic group. The research goal identified by the authors is to conduct an analysis of the identities of the ethnic groups of India, Middle East, and African and European countries to identify their characteristic features and sources, as well as examine them as a sociocultural factor in the system of ethnic conflict origin and development. The theoretical basis is composed of a set of scientific papers examining the process of the formation of ethnic groups and conflicts, sociological survey results, and statistical data. The methodological foundation of the study is formed by the retrospective analysis of scientific works revealing the process of ethnic group formation and the systematic approach that allowed identifying and justifying the role of identity in the genesis of ethnic groups and the structure of modern ethnic conflicts. The epistemological potential of statistical and sociological methods of quantitative and qualitative research made it possible to adequately interpret the current scientific research results regarding the hypothesis proposed by the authors. The novelty of the study and its results are determined by the original approach towards identifying the characteristic features of identity and studying its systemic relationships with the nature of modern ethnic conflicts. The results acquired in the course of the study support the conclusion that identity plays a significant role in the process of ethnic group formation, is closely intertwined with other characteristics of ethnos, and contains a specific structure of elements classified by the authors into three groups. In the context of the formation of dangers and threats to the identity, the ethnic group takes comprehensive action to counter it, which ultimately leads to the emergence and development of the ethnic conflict.